Robust combined feedback/feedforward control for fractional FOPDT systems - Padula, Fabrizio; Visioli, A. (John Wiley and Sons, 2016)
Copyright © 2015 John Wiley & Sons, Ltd.In this paper, a combined feedback/feedforward design methodology is proposed for fractional systems in order to cope with model uncertainty and to minimize performance degradation. Based on a fractional commensurate uncertain model, a parametric robust controller is first designed. Then, a parametric command signal for the unity feedback loop is designed. Finally, an optimal set of tuning parameters is found by solving a constrained min–max optimization problem in order to minimize the worst-case settling time. Simulation results show the effectiveness of the methodology. Copyright © 2015 John Wiley & Sons, Ltd.